Governmentality in Gabriel Garcia Marquez's One of These Days - Pasopati, Rommel Utungga; Ramadhani, Anggraeni; Salsabila, Anindya Thalita; Putri, Alvina Salshabilla Linjani; Agil, Agischa Putri (Pioneer: Journal of Language and Literature, 2024)
This paper exposes power relations of governmentality in Gabriel Garcia Marquezâ€™s short story â€œOne of These Daysâ€. Marquezâ€™s story tells about asymmetric relations between a dentist and his cityâ€™s Mayor. The writing must be analyzed through Michel Foucaultâ€™s concept of governmentality, in which power is rationalized in shaping disciplines and anti-resistance. Through the qualitative method, this article explores the accentuations of governmentality in Gabriel Garcia Marquezâ€™s â€œOne of These Daysâ€. Throughout the close reading as the technique of collecting data and content analysis as the technique of data analysis, the analysis includes what the city Mayor does in governmentality as forceful power against the dentist. Governmentality is seen in how corrupt behaviour affects subordinate people by implementing power and discipline. In conclusion, governmentality plays a significant role in Marquezâ€™s story since it shows how power is not static but grows through the abusive behaviour of the subjectâ€™s power through the discipline of the object.